Passeggiando per la Federico II - Castagnaro, Alessandro (Fuori collana, 2023)
The second updated edition of this volume, produced in Italian and English, aims to raise awareness of the incidence and importance of Federico II University's different locations in both the Naples metropolitan area and the regional contexts. This publication was made on the occasion of the 800th anniversary of Federico II, which will be on June 5, 2024. The sites of Federico II, collected in this volume and described by colleagues from our University's architectural history area, are strongly linked to the city's history, from the early Middle Ages to the modern and contemporary ages. In fact, through their description, events related to civil, political, and art history emerge with the evolution of taste and different artistic forms. The publication aims to make people understand the significant role of the Federico II sites, from the oldest part of the city's historic center to the most recent ones that have been added to the already vast Frederico II heritage - such as the sites of Scampia, Bacoli, Avellino, Castel Volturno, and Torre Lama in Salerno area. A further objective is to emphasize how these valuable architectures, rich in diffuse artistry, are preserved, re-functionalized, enhanced, and offered for the fruition of a large public thanks to the University.